Utilization of Artificial Intelligence in Chatbot Development for New Student Admission Support at Cokroaminoto University Palopo - Muhammad Akram Hamzah; Siaulhak Siaulhak; Iriansa Iriansa; Andi Jumardi; Andryanto Aman (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This research aims to develop an artificial intelligence-based chatbot as a support tool for the New Student Admission (PMB) process at Cokroaminoto University Palopo. The system development method applied is the waterfall method, which consists of analysis, design, implementation, testing, and maintenance stages. The main focus of this research is to design and implement a chatbot that is able to provide information and support to prospective new students throughout the admission process. In the analysis stage, user needs and scenarios were identified to guide the development of the chatbot. System design includes the selection of artificial intelligence algorithms and a friendly user interface. Implementation involves developing a chatbot prototype that utilizes artificial intelligence technology. The expected results can improve the efficiency and quality of new student admission services at Universitas Cokroaminoto Palopo.